Bridging Tradition and Technology: A Systematic Review of Digital Innovations in Cultural Heritage Preservation - Siti Hafizah, Suaidi; Nur Auni, Ugong; Syahrul Nizam, Junaini; Ahmad Nizar, Yaakub; Khalid, Zanudin; Bazley Bee, Basrah Bee (UMT PRESS, 2026)
This study evaluates the integration of advanced technological tools for the purpose of preserving a cultural heritage, emphasising innovative strategies relevant to the digital era. Despite considerable technological advancements, significant gaps remain regarding the full implications of these tools for data preservation and long-term accessibility. Consequently, this research investigates how advanced technologies can effectively enhance preservation practices and overcome existing challenges. Specifically, it analyses core themes such as the efficacy of digital technologies, levels of public engagement, sustainability considerations, integration barriers, and strategic investment opportunities. the findings highlight that tools such as artificial intelligence (AI), photogrammetry, and virtual reality (VR), substantially enhance heritage documentation accuracy and accessibility. Nevertheless, persistent issues related to data preservation and consistent accessibility warrant continued investigation. This systematic review critically analyses 50 selected articles from an initial dataset of 2,476 articles using the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) framework. The study also emphasises the value of existing initiatives such as 4CH and Twin-IT, underscoring the need for harmonising traditional preservation techniques with innovative digital solutions, thereby offering essential guidance for future cultural heritage preservation efforts.